Drivers' acceptance of mobile navigation applications: An extended technology acceptance model considering drivers' sense of direction, navigation application affinity and distraction perception. Issue 145 (January 2021) - Yang, Liping; Bian, Yang; Zhao, Xiaohua; Liu, Xiaoming; Yao, Xianglin
Highlights: The extended TAM model explained 60.50% of the variance in the intention to use. Navigation application affinity and distraction perception were effective predictors of intention. Navigation application affinity and distraction perception also affected use perceptions. Sense of direction was a significant individual trait affecting drivers' perceptions. Abstract: This study proposes an integrated technology acceptance model to investigate the factors that affect drivers' usage intention of mobile navigation applications. The proposed model adds three new constructs (drivers' sense of direction, navigation application affinity and distraction perception) to the original technology acceptance model based on the features of mobile navigation applications. First, a questionnaire was developed and administered, and data from 384 drivers were collected via an online survey. Second, confirmatory factor analysis was conducted to examine the reliability and validity of the developed scale based on the collected data. Third, a structural equation model was constructed to investigate the interrelationships among these constructs in the conceptual research model and to identify the key factors that affect drivers' acceptance of mobile navigation applications. The proposed model explained 60.50% of the variance in the intention to use mobile navigation applications. In addition to attitude and perceived usefulness, navigation application affinity and distraction perception also significantly affected drivers' intention to use mobile navigation applications. Navigation application affinity and distraction perception affected not only drivers' intention to use but also their perceptions. Sense of direction was a significant individual trait that affected drivers' navigation application affinity, distraction perception, perceived ease of use and perceived usefulness. These findings imply that relevant developers should continually optimize the incorrect and inappropriate use of navigation information and that they should attach importance to the amount and intelligibility of navigation information. Furthermore, the prompt form of navigation information should satisfy the demands and expectations of drivers with different senses of direction. Overall, this study improves our understanding of drivers' acceptance of mobile navigation applications and provides some important practical implications to improve mobile navigation services.